Effect of reactive flexible rejuvenators on thermal-oxidative aging resistance of regenerated SBS modified asphalt. (20th December 2022) - Han, Xiaobin; Mao, Sanpeng; Zeng, Shangheng; Duan, Hao; Liu, Quantao; Xue, Lihui; Yu, Jianying
Abstract: The high-quality regeneration of aged SBS modified asphalt could promote to achieve the objective of low-carbon development. In this study, to reconstruct the structure of aged SBS, two kinds of reactive flexible rejuvenator (RFRs) named T-PEG and T-HTPB were synthesized from 2, 4-toluylene di-isocyanate, polyethylene glycol and hydroxyl terminated polybutadiene. The ordinary regenerated SBS modified asphalt (RSBSMA) and reactive RSBSMA were prepared by using aromatic hydrocarbon oil (AO) and (T-PEG/T-HTPB + AO) respectively. Afterward, the chemical structures and physio-rheological performance of RSBSMAs after short-term and long-term thermal-oxidative aging were explored. The results of Fourier transform infrared spectra showed that the butadiene and ether bond indices of reactive RSBSMA decreased significantly after aging, indicating that T-HTPB regenerated SBS mainly suffered the breaking of carbon-carbon double bonds, while the degradation of segments with ether bonds appeared in SBS restored by T-PEG. The carbonyl and sulfoxide indices of reactive RSBSMA were lower than those of ordinary RSBSMA, revealing that the effect of thermal-oxidative aging on asphalt was prevented by the restoration of aged SBS structure. The changing amplitude of physical and rheological properties of reactive RSBSMA after aging was less than that of ordinary RSBSMA, which confirmed that the aging resistance of reactive RSBSMA was stronger than that of ordinary RSBSMA due to the repair of aged SBS structure. Different RFRs could offer diverse anti-aging abilities on reactive RSBSMA. The research results suggested that T-PEG rather than T-HTPB was a better choice as a reactive rejuvenator of aged SBS modified asphalt.